Promoting Local Ownership: Lessons Learned from Process of Transitioning Clinical Mentoring of HIV Care and Treatment in Ethiopia - Kassie, Getnet M.; Belay, Teklu; Sharma, Anjali; Feleke, Getachew (Frontiers in Public Health, 2018)
Introduction Focus on improving access and quality of HIV care and treatment gained acceptance in Ethiopia through the work of the International Training and Education Center for Health. The initiative deployed mobile field-based teams and capacity building teams to mentor health care providers on clinical services and program delivery in three regions, namely Tigray, Amhara, and Afar. Transitioning of the clinical mentoring program (CMP) began in 2012 through capacity building and transfer of skills and knowledge to local health care providers and management. Objective The initiative explored the process of transitioning a CMP on HIV care and treatment to local ownership and documented key lessons learned. Methods A mixed qualitative design was used employing focus group discussions, individual in-depth interviews, and review of secondary data. The participants included regional focal persons, mentors, mentees, multidisciplinary team members, and International Training and Education Center for Health (I-TECH) staff. Three facilities were selected in each region. Data were collected by trained research assistants using customized guides for interviews and with data extraction format. The interviews were recorded and fully transcribed. Open Code software was used for coding and categorizing the data. Results A total of 16 focus group discussions and 20 individual in-depth interviews were conducted. The critical processes for transitioning a project were: establishment of a mentoring transition task force, development of a roadmap to define steps and directions for implementing the transition, and signing of a memorandum of understanding (MOU) between the respective regional health bureaus and I-TECH Ethiopia to formalize the transition. The elements of implementation included mentorship and capacity building, joint mentoring, supportive supervision, review meetings, and independent mentoring supported by facility-based mechanisms: multidisciplinary team meetings, case-based discussions, and catchment area meetings. Conclusion The process of transitioning the CMP to local ownership involved signing an MOU, training of mentors, and building capacity of mentoring in each region. The experience shed light on how to transition donor-supported work to local country ownership, with key lessons related to strengthening the structures of regional health bureaus, and other facilities addressing critical issues and ensuring continuity of the facility-based activities.